Extended Tanh-Function Method for Solving Traveling Wave Solutions of Nonlinear Kundu Equation (Communications in Mathematical Research, 2021)
In this paper, by using the balancing method and the extended tanh-function method, we obtain the exact traveling wave solutions of Kundu equationwith fifth-order nonlinear term. Applications of this method to some other nonlinearpartial differential equations are also presented.
Keywords: extended tanh-function method; Kundu equation; traveling wave solution.